Admission albumin-globulin ratio associated with delayed cerebral ischemia following aneurysmal subarachnoid hemorrhage - Guo, Xiumei; Xiong, Yu; Gao, Wen; Huang, Xinyue; Zheng, Hanlin; Wu, Huiqiang; Jiang, Xutang; Lin, Qingxin; Xiao, Yinfeng; Liu, Qiaoling; Pan, Zhigang; Chen, Chunhui; et al. (Frontiers in Neurology, 2024)
Background Despite the widespread use in ischemic stroke, cancer, and malnutrition, the predictive ability of serum albumin to globulin ratio (A/G) among patients suffering from aneurysmal subarachnoid hemorrhage (aSAH) remains unknown. This study aimed to determine if serum A/G ratio is associated with the occurrence of delayed cerebral ischemia (DCI) after aSAH. Methods We retrospectively viewed the medical records of aSAH patients from 08/2017 to 08/2022. Serum albumin and globulin laboratory test results were collected within 24 hours after admission. Serum A/G were dichotomized based on whether the DCI occurred. Logistic regression was used to determine the predictors of DCI. The relationship between serum A/G and the occurrence of DCI was analyzed with receiver operating characteristic(ROC) curve. Results A total of 363 eligible patients with aSAH were included in the study, among which DCI occurred in 87 patients(23.97%). Serum A/G[OR=2.720, 95%CI (1.190-6.270), P=0.018], non-surgical[OR=0.228, 95%CI (0.065-0.621), P=0.008], lactate dehydrogenase[OR=1.004, 95%CI (1.000-1.008), P=0.029], P[OR=0.354, 95%CI (0.130-0.926), P=0.038], plasma fibrinogen[OR=1.266, 95%CI (1.019-1.583), P=0.035] were associated with the occurrence of DCI. ROC showed that serum A/G, non-surgical, LDH, P, plasma fibrinogen could predict the occurrence of DCI in aSAH patients with values 0.575, 0.560, 0.602, 0.571 and 0.539 for serum A/G, non-surgical, LDH, P, plasma fibrinogen, respectively. Conclusions In conclusion, serum A/G levels are correlated with DCI in individuals with aSAH, and high serum A/G levels on admission may be associated with the occurrence of DCI.